1 GAMBARAN FUNGSI KOGNITIF PADA LANSIA DI TIGA YAYASAN MANULA DI KECAMATAN KAWANGKOAN - Ramadian, Daniar Aprilia (e-CliniC, 2013)
AbstractBackground: An increasing number of elderly people raises various social, economic, and health problems. Health problems are often occur in the elderly is impaired cognitive function. The rapid examination and practical, high value is the examination of the Mini Mental State Examination (MMSE) and Trail Making Test (TMT). These checks are done by giving series of commands at someone and assess their accuracy.Objective: To knowing overview of cognitive function in the elderly at three elderly people foundation in district Kawangkoan by sex, age, and education.Methods: The descriptive research with cross-sectional method, was conducted in November 2012 held at the Elderly Foundation Centre Kawangkoan Minahasa, Maupusan Foundation, and Pakakamangen Foundation in District Kawangkoan.Results: From the research gained 61 people who met the inclusion criteria consisted of 4 men and 57 women. Based on age, and education level showed decline in cognitive function is most at 75-90 years old and last education level is Elementary School.Conclusion: The results of the MMSE and TMT in the elderly at three elderly people foundation in district Kawangkoan mostly with normal results on the MMSE and TMT abnormal.Keywords: Elderly, cognitive function, MMSE, TMT-A & B.AbstrakLatar belakang: Peningkatan jumlah penduduk lanjut usia menimbulkan berbagai masalah sosial, ekonomi, dan kesehatan. Masalah kesehatan yang sering terjadi pada usia lanjut ialah gangguan fungsi kognitif. Pemeriksaan yang cepat dan praktis namun nilainya tinggi adalah pemeriksaan Mini Mental State Examination (MMSE) dan Trail Making Test (TMT). Pemeriksaan ini dilakukan dengan memberi serangkaian perintah pada seseorang dan menilai ketepatannya.Tujuan: Untuk mengetahui gambaran fungsi kognitif pada lansia di tiga yayasan manula di kecamatan kawangkoan berdasarkan jenis kelamin, umur, dan pendidikan.Metode: Penelitian deskriptif dengan metode potong lintang, dilaksanakan pada bulan November 2012 bertempat di Yayasan Manula Pusat Kawangkoan Minahasa, Yayasan Maupusan, dan Yayasan Pakakamangen di Kecamatan Kawangkoan.Hasil: Dari penelitian diperoleh 61 orang yang memenuhi kriteria inklusi terdiri dari 4 laki-laki dan 57 perempuan. Berdasarkan usia, dan tingkat pendidikan menunjukkan penurunan fungsi kognitif terbanyak adalah pada usia 75-90 tahun dan tingkat pendidikan terakhir SD.Kesimpulan: Hasil pemeriksaan MMSE dan TMT pada lansia di tiga yayasan manula di kecamatan Kawangkoan sebagian besar dengan hasil normal pada MMSE dan abnormal pada TMT.Kata kunci: Lansia, fungsi kognitif, MMSE, TMT-A & B.